The effect of music-supported acceptance and commitment therapy on perceived stress and pain in cancer patients - Tan, Mehtap; Karakas, Sibel Asi; Ekinci, Mine; Ersogutcu, Filiz; Aksoy, Asude (Assoc Medica Brasileira, 2025)
OBJECTIVE: The aim of this study was to investigate the effect of music-supported acceptance and commitment therapy on perceived stress and pain levels in cancer patients. METHODS: Atotal of 79 cancer patients participated in this controlled, pre-test/post-test quasi-experimental study (experimental group: n=29; control group: n=50). The intervention group received eight sessions of acceptance and commitment therapy with music, while the control group received standard care. Data were collected using the Perceived Stress Scale and the West Haven-Yale Multidimensional Pain Inventory. RESULTS: The post-test Perceived Stress Scale scores of the experimental groupwere statistically significantly lower compared tothe control group (26.17 +/- 3.52 vs. 28.88 +/- 5.73, p<0.05), indicating a reduction in perceived stress. Additionally, there was a statistically significant difference in pain severity scores between the groups (9.62 +/- 2.33 in the experimental group vs. 8.06 +/- 3.14 in the control group, p<0.05). The effect size for stress reduction was moderate (Cohen's d=-0.54). CONCLUSION: This study revealed that a music-supported acceptance and commitment therapy reduced perceived stress, pain severity, and pain interference in cancer patients. Nurses should actively involve non-pharmacological methods in pain and stress management planning in collaboration with patients and their families. They should create a therapeutic environment and take necessary measures to enable patients to benefit from non-pharmacological interventions.
Keywords: Acceptance and commitment therapy; Cancer; Nursing; Pain; Psychological stress